Containment of a cluster of COVID-19 to prevent impending community transmission: experience from a rural area in South India - Nallat, Divyamol; C., Sreedevi (International Journal of Research in Medical Sciences, 2022)
Background: On 23 July 2020, COVID-19 contact tracing cell was informed of a laboratory confirmed case of COVID-19 with substantial number of contacts. The current scenario under investigation is an example for a large outbreaks amenable to containment. If not contained immediately and effectively it may pass on to large community transmission. Methods: Epidemiological investigation and contact tracing was carried out to identify the source and contacts of a confirmed case of COVID-19 reported on 22 July 2020. A semi-structured questionnaire prepared by COVID-19 contact tracing cell, Government Medical College (GMC), Palakkad was used to collect data on clinical characteristics, likely source of exposure and contacts made by the index case. High risk and low risk contacts were contacted over telephone to ensure quarantine, testing on 8th day (both for high risk contacts) and symptom monitoring. Results: Total of 55 high risk contacts were identified, 15 of which were of high risk exposure. All 15 high risk contacts were kept in quarantine with testing on day 8 after last exposure. 7 new cases occurred among 15 the high risk contacts of which one turned out to be suspected primary, 5 secondary cases of index case and one secondary case of the suspected primary case. All secondary and low risk contacts were kept under symptom surveillance, and did not develop COVID-19. Conclusions: Timely case notification coupled with complete and effective contact tracing and quarantining has contained the cluster and prevented it from emerging as large community transmission.